Hepato-protective effects of Glossogyne tenuifolia in Streptozotocin-nicotinamide-induced diabetic rats on high fat diet - Shibu Marthandam Asokan; Ruoh-Yuh Wang; Tsu-Han Hung; Wan-Teng Lin (BMC, 2019)
Abstract Background Glossogyne tenuifolia (GT) is a traditional herbal tea in Penghu Island, Taiwan. Its extract is traditionally been used as an antipyretic, hepatoprotective and anti-inflammatory remedy in folk medicine among local residents. The present study investigated whether GT could improve streptozotocin-induced acute liver injury of type 2 diabetes mellitus. Methods Male Wistar rats aged eight weeks were induced to be hyperglycemic by the subcutaneous injection of streptozotocin-nicotinamide (STZ-NA) and a combination of a high-fat diet (HFD) (N group). The animals were given GT extracts at a low dose (50 mg/kg) (L group) or a high dose (150 mg/kg) (H group) or an anti-diabetic drug (acarbose) (P group) in drinking water for 4 weeks. Results The results revealed that STZ-NA increased hepatomegaly, hepatocyte cross-sectional area, hypertrophy-related pathways (IL6/STAT3-MEK5-ERK5, NFATc3, p38 and JNK MAPK), proapoptotic molecules (cytochrome C, cleaved caspase-3), and fibrosis-related pathways (FGF-2, pERK1/2). These pathway components were then expressed at lower levels in the L and H group when compared with the N group. The liver-protective effect of GT in STZ-NA-induced diabetic rats with hyperlipidemia was through an enhancement in the activation of the compensatory PI3K-Akt and Bcl2 survival-related pathway. Conclusion The results demonstrate that the hot water extracts of GT efficiently ameliorates the STZ-NA-induced diabetes associated liver damage in rat models.